Design of a Robust Coordinated Power Oscillation Damper for Use with Large-Scale Wind Energy System Connected to a Multimachine Power System - Paul Kabiru; Keren Kaberere; Stanley Kamau (Journal of Electrical and Computer Engineering)
Many researchers have proposed the use of the doubly fed induction generator (DFIG)-based wind energy conversion system (WECS) in the enhancement of power system dynamic performance. However, the application of a coordinated design strategy to coordinate the DFIG and other synchronous generators in the system for the improvement of small-signal stability is rarely researched. What is more, the use of strategy with a low computational burden to enhance the robustness of coordinated strategy for the design of damping controllers is rare. A coordinated strategy in designing multiple damping controllers, including DFIG-based power oscillation damper (POD) and power system stabilizers (PSSs), is proposed in this paper. A modal participation factor is employed to find out the most effective feedback signal for the POD. A hybrid optimization algorithm based on the grey wolf optimizer (GWO) and particle swarm optimizer (PSO) is applied for parameter optimization of the damping controllers considering a multiobjective eigenvalue-based optimization problem. Modal analysis is carried out on the widely studied two-area four-generator benchmark power system to establish the theoretical viability of the proposed approach. Probabilistic analysis established on Monte Carlo simulation is then carried out to prove the robustness of the coordinated design strategy under diverse operating conditions. Nonlinear time-domain simulations are used to verify the damping performance and robustness of the proposed strategy under different operating scenarios.